Performance Measurement of Local Government in Indonesia: A Conceptual Study - Putri, Lovina Eka; Aswar, Khoirul; Ermawati (Information Management and Business Review, 2020)
This study begins with the problem of the many Indonesia’s local governments that have not been able to compile a Government Agency Performance Accountability Report or LAKIP. This is because there are still many local governments that have not been able to measure performance with applicable standards. And therefore, many local governments still get poor grades in preparing their LAKIP. This due to several factors such as the commitment of management which is still questionable, the lack resources used to measure performance and so forth. This study aims to find out how far have local government efforts are taken to measure performance according to organizational factors of local government in Indonesia specifically in Bekasi. Through the institutional theory, this study has three objectives, to find out the effects of technical knowledge, management commitment, and resources on performance measurement. Therefore, this study contributes to provide a picture for the local government in measuring performance based on organizational factors.